Lipid pro.ling of developing Jatropha curcas L. seeds using 1H NMR spectroscopy - Annarao, S.; Sidhu, O.P.; Roy, R.; Tuli, R.; Khetrapal, C.L.
Seed development in Jatropha curcas L. was studied with respect to phenology, oil content, lipid pro.le and concentration of sterols. Seeds were collected at various stages of development starting from one week after fertilization and in an interval of .ve days thereafter till maturity. These were classi.ed as stage I to stage VII. Moisture content of the seeds ranged from 8.8 to 90.3
Keywords: JATROPHA CURCAS; 1H NMR; STEROLS; DEVELOPING SEED